Activism as a Way of Life: The Social World of Social Movements in Middle-Class Beirut - Chamas, Sophie (PARTECIPAZIONE E CONFLITTO, 2021)
This article concerns itself with why and how activists persevere and manage to reproduce themselves as activists in contexts where they experience what is described as routine "failure", taking Lebanon’s activist scene as its focus. Drawing on ethnographic fieldwork carried out when Lebanon’s civil society was dominated by members of the country’s cosmopolitan professional middle class, I emphasise the affective dimensions of activism, the role that personal desires, emotions and anxieties play in enabling activists to persist in the most stagnant of conjunctures but that also, at the same time, keep them from advancing their agendas.